Natural discharge measures from bridges with piers - Priego-Hernández, Gastón; Vázquez-Vázquez, Leydi; Cabrera, Luis Antonio; Rivera-Trejo, Fabián (Ecosistemas y Recursos Agropecuarios, 2022)
Measuring a river discharge from bridges with piers has been questioned. However, here, it is shown that now it is feasible to do it without losing accuracy using acoustic Doppler equipment. The objectives of this work were to analyze the possibility of measuring from bridges with piers with acoustic Doppler equipment and find if there is a difference between measuring upstream or downstream of the bridge. The discharge rate, the plain view, and cross-section hydrodynamics were evaluated and compared analytically and graphically in each section. Also, the intensity of the sus- pended sediments in each area was assessed. The results showed that the difference between measuring upstream or downstream of a bridge is less than 1.5%. Hydrodynamically, a difference in flow direction was obtained due to the curvature of the river and the bridge’s piers, but it does not affect the flow discharge measurement.